Difficulties experienced by higher education teachers during the COVID-19 pandemic - Santos, Jennifer Thalita Targino dos; Assuncao-Luiz, Alan Vinicius; Pereira, Alison Luis Eburneo; Luciano, Anderson Ricardo Malmonge Barbosa [UNESP]; Carvalho Filho, Idinei Francisco Pires de [UNESP]; Santos, Milena Jorge Simoes Floria Lima; Garbin, Monica Cristina (Organizacion Estados Iberoamericanos Educacion Ciencia & Cultura-oei, 2022)
The COVID-19 pandemic changed the schedule of activities proposed for the academic year 2020-21, in which face-to-face classes were replaced by emergency remote teaching (ERE). For higher education professors, although good teaching practices are a constant concern of universities, challenges have arisen due to the sudden transition and implementation of the ERE. For this reason, this study aimed to investigate the main difficulties encountered by higher education professors in Brazil, dealing with the ERE during the COVID-19 pandemic. Data collection took place between December 2020 and February 2021, using a electronic questionnaire consisting of 19 objective questions. 234 professors participated in the study, of which 77.4% of the participants had difficulties during the adaptation process for the ERE, and are related to the lack of training or technological resources given by the institutions; problems with the use of digital technologies (tools and software); influence of psychological difficulties; difficulties associated with administrative bureaucracy or with Data Security. It is clarified that the transition must be carried out with planning and investment in the adequate training of teachers, so that education in a virtual context achieves the same success as face-to-face meetings.
Keywords: Pedagogical difficulties; Emergency remote learning; Pandemics; COVID-19; Pedagogical methodologies; Digital technologies